Public Higher Education Studies: Developing a Multicultural-Based Islamic Religious Education Learning Model - Syafei, Imam; Wasehudin, Wasehudin; Kesuma, Guntur Cahaya; Septuri, Septuri; Frimayanti, Ade Imelda (Universitas Islam Negeri Raden Intan Lampung, 2020)
The purpose of this study was to develop a multicultural-based Islamic religious education learning model to develop students’ religious tolerance in Lampung and Banten Provinces. This study employed the research and development design. The research data was obtained by employing questionnaires and observations. The questionnaires and observations were administered to thirty-six Lampung University students as the experimental class and thirty-six Sultan Ageng Tirtayasa University students as the control class. The data were analyzed using gain analysis and independent sample t-test. This study produced a multicultural-based Islamic religious education learning model to develop students' religious tolerance attitudes in the Provinces of Lampung and Banten. There were differences in the radicalism attitude of students who used and those who did not use the developed multicultural-based Islamic religious education learning model in Lampung and Banten Provinces. It is suggested for further researchers to apply a multicultural learning model in Islamic religious education at the elementary, junior high, and senior high school levels.